1995
DOI: 10.1177/030089169508100104
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Fine-Needle Aspiration Cytology. of the Breast-Multicenter Study of 23,063 Aspirates in ten Italian Laboratories

Abstract: Although centers scored, on average, well within standards recommended by national authorities, this study suggests the opportunity of interlaboratory quality control to achieve more homogeneous criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 1 publication
1
16
0
3
Order By: Relevance
“…Case studies of consecutive FNAB in centers have emphasized the diagnostic accuracy and do not usually distinguish breast carcinomas according to their histologic subtype. A large retrospective study from Italy evaluating more than 20,000 breast FNAB at multiple medical centers showed that the sensitivity was associated with histologic types of breast cancer, with lower sensitivity for intraductal carcinoma (77 vs. 92.9%, p < 0.00001) and lobular type compared to other types of invasive carcinoma (85.5 vs. 94%, p < 0.0025) [40]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Case studies of consecutive FNAB in centers have emphasized the diagnostic accuracy and do not usually distinguish breast carcinomas according to their histologic subtype. A large retrospective study from Italy evaluating more than 20,000 breast FNAB at multiple medical centers showed that the sensitivity was associated with histologic types of breast cancer, with lower sensitivity for intraductal carcinoma (77 vs. 92.9%, p < 0.00001) and lobular type compared to other types of invasive carcinoma (85.5 vs. 94%, p < 0.0025) [40]. …”
Section: Resultsmentioning
confidence: 99%
“…In a study of 1885 nonpalpable breast lesions, Boerner et al [36] found a ROM in cases reported as atypical of 52.9%, falling in between the ROM of suspicious (75.8%) and benign (3.7%). Using a definition close to the currently proposed definition of atypical breast cytology, that is, “minor atypias, not consistent with cancer though sufficient to advise open biopsy,” Ciatto et al [40] reported a PPV of 53.4% for atypical as an average in their multicenter retrospective study, compared to a PPV of 96.9% for malignant breast cytology. Aker et al [31] distinguished several atypical categories, atypical/probably benign with ROM of 0% ( n = 24), atypical/not otherwise specified with ROM of 75% ( n = 60) and atypical/probably malignant with ROM of 97% in their consecutive series of 733 breast FNAB with histologic follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular a C3 (atypical) or C4 (suspicious) report on FNAC [1,2], respectively associated with a 20-50% or 90-95% PPV, do not allow immediate treatment planning, usually need histological confirmation, and may cause unnecessary benign surgical biopsies. Relative to the histological information obtained through core biopsy, especially within the context of assessing screen-detected lesions, breast FNAC has thus become increasingly abandoned particularly in North America and the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Die Feinnadelpunktion (FNP) hat einen hohen Stellenwert in der Differentialdiagnose von palpablen Mammaläsionen [1] und wird auch zur Verbesserung der diagnostischen Sicherheit bei nicht palpablen Läsionen, alternativ stereotaktisch [2,3] oder US-gesteuert [4], eingesetzt. Die Vorteile der FNP sind insbesondere die mögli-che sofortige Diagnose, die minimale Kompromittierung des Tumorbetts bei malignen Läsionen und die im Vergleich geringen Kosten [5].…”
Section: Introductionunclassified